2015
DOI: 10.1007/s11251-015-9344-y
|View full text |Cite
|
Sign up to set email alerts
|

Scientific reasoning abilities in kindergarten: dynamic assessment of the control of variables strategy

Abstract: A dynamic assessment tool was developed and validated using Mokken scale analysis to assess the extent to which kindergartners are able to construct unconfounded experiments, an essential part of scientific reasoning. Scientific reasoning is one of the learning processes happening within science education. A commonly used, hands-on, experimentation task was adapted to dynamically assess the use of the so-called control of variables strategy (CVS) by children 4 to 6 years of age. In this task, the children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 50 publications
8
57
0
Order By: Relevance
“…When kindergartners have to predict and explain what side of a balance beam would go down, their performance decreases when they have to incorporate distance (to the fulcrum), besides weight, in their predictions and explanations (Siegler, 1976). Another study on scientific reasoning of kindergartners found that children design fewer experiments correctly when the number of variables they have to set increases ( Van der Graaf, et al, 2015). The level of the game-play also related to game exploration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When kindergartners have to predict and explain what side of a balance beam would go down, their performance decreases when they have to incorporate distance (to the fulcrum), besides weight, in their predictions and explanations (Siegler, 1976). Another study on scientific reasoning of kindergartners found that children design fewer experiments correctly when the number of variables they have to set increases ( Van der Graaf, et al, 2015). The level of the game-play also related to game exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Besides attentional control, nonverbal reasoning related to game efficiency. Many types of reasoning have been found to be involved in scientific thinking, such as nonverbal reasoning ( Van der Graaf, et al, 2015), syllogistic reasoning (Wagensveld, et al, 2015), and general fluid ability (Mayer, Sodian, Koerber, & Swippert, 2014). As Dunbar and Klahr (2012) have…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations